2014
DOI: 10.1186/1471-2458-14-s3-s1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pregnancy experiences and contraceptive knowledge among single adults in a low socio-economic suburban community in Kuala Lumpur, Malaysia

Abstract: BackgroundThis study aimed to investigate the prevalence of pregnancy experience and its association with contraceptive knowledge among single adults in a low socio-economic suburban community in Kuala Lumpur, Malaysia.MethodsA cross-sectional survey was conducted in 2012 among the Kerinchi suburban community. Of the total 3,716 individuals surveyed, young single adults between 18 and 35 years old were questioned with regard to their experience with unplanned pregnancy before marriage. Contraceptive knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…First, the credibility of this study as a medical record review lies on the reliability and completeness of the clinical data. The missing values of the variables in this study ranged from 0 to 26%, which were lower than the data used in our prior study [16], mainly because of the revised data abstraction format and the implementation of the electronic data collection method [35]. Second, although we have collected data regarding the family issues behind the abuse and violence and the mental health impact on women, the information contained in the medical records is limited.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…First, the credibility of this study as a medical record review lies on the reliability and completeness of the clinical data. The missing values of the variables in this study ranged from 0 to 26%, which were lower than the data used in our prior study [16], mainly because of the revised data abstraction format and the implementation of the electronic data collection method [35]. Second, although we have collected data regarding the family issues behind the abuse and violence and the mental health impact on women, the information contained in the medical records is limited.…”
Section: Discussionmentioning
confidence: 92%
“…Cohabitation is traditionally viewed as a “trial marriage”. Using the natural selection theory, partners exhibiting low level or no violence may be more likely to enter into marriage, whereas cohabitating women living in abusive relationships may tend to stay in cohabitating relationships [16]. Alternatively, the Power–Control Theory stipulates status incompatibilities in intimate partner relationships might lead to lower marital satisfaction and even IPV [1820].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, general practitioners in India were reported to be reluctant to provide contraceptives to girls under the age of 16 as it was against their cultural values. 10,11 Also, a report from a study from Ibadan in Nigeria showed a cultural reluctance towards providing contraceptives to unmarried adolescents as more than half of HCPs perceived the provision of contraceptives to such clients as promoting sexual promiscuity. 12 In a study conducted in Kenya and Zambia, midwives were hostile to adolescent reproductive services, but continuing education on adolescent sexuality and reproduction reversed their negative opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Poor knowledge about contraception and its consistent usage has been found to contribute to the high incidence of unwanted pregnancy and STIs. 7 In order to reduce the risks and public health problems associated with unwanted pregnancy and STIs, it is important to advocate the use of dual contraception among young women with risky sexual behavior. Therefore, our aim is to explore the knowledge, awareness, and factors associated with the use of dual contraception as a means of preventing both STIs and unwanted pregnancy among female undergraduates in Ibadan, Nigeria.…”
Section: Introductionmentioning
confidence: 99%